2020
DOI: 10.15293/1813-4718.2101.11
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of Video Materials for Teaching Deaf and Hard of Hearing Students

Abstract: Problem and aim. The paper deals with the problem of adapting educational video materials for teaching deaf and hard-of-hearing students. The paper is aimed at identifying and justifying the theoretical bases for adaptation of video materials for teaching students with hearing impairment both during in-class learning and self-study. Methodology. The study was conducted at the Centre for inclusive education of Kalashnikov Izhevsk State Technical University, the experiment involved 11 hearing-impaired students m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Similar tests conducted in English gave similar results, with the difference between the graphical and textual representation of the information being even more significant . The analysis of the obtained results (Student's t-test) showed that the difference between the obtained results on the use of different types of dubbing is statistically significant (Krasavina et al, 2021).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Similar tests conducted in English gave similar results, with the difference between the graphical and textual representation of the information being even more significant . The analysis of the obtained results (Student's t-test) showed that the difference between the obtained results on the use of different types of dubbing is statistically significant (Krasavina et al, 2021).…”
Section: Resultsmentioning
confidence: 94%
“…Most of the students said that they do not have time to simultaneously monitor and correlate the image on the screen and sign interpretation. The difference in the speed of perception and processing of text subtitles and sign language interpretation can be explained by important differences between sign language and Russian (in this case, written) (Krasavina, Ponomarenko, Serebryakova, Zhuykova, 2021).…”
Section: Discussionmentioning
confidence: 99%